Critical exponents for a transition from integrability to non-integrability via localization of invariant tori in the Hamiltonian system - Leonel, Edson Denis [UNESP]; de Oliveira, Juliano A. [UNESP]; Saif, Farhan [UNESP] (Iop Publishing Ltd, 2011)
Critical exponents that describe a transition from integrability to non-integrability in a two-dimensional, nonlinear and area-preserving map are obtained via localization of the first invariant spanning curve (invariant tori) in the phase space. In a general class of systems, the position of the first invariant tori is estimated by reducing the mapping of the system to the standard mapping where a transition takes place from local to global chaos. The phase space of the mapping shows a large chaotic sea surrounding periodic islands and limited by a set of invariant tori whose position of the first of them depends on the control parameters. The formalism leads us to obtain analytically critical exponents that describe the behaviour of the average variable (action) along the chaotic sea. The result is compared to several models in the literature confirming the approach is of large interest. The formalism used is general and the procedure can be extended to many other different systems.